2004
DOI: 10.1152/jn.00947.2003
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Age-Related Changes in Properties of Motor Units in the Gastrocnemius Muscle of Rats

Abstract: Sugiura, Miho and Kenro Kanada. Progress of age-related changes in properties of motor units in the gastrocnemius muscle of rats. J Neurophysiol 92: 1357-1365, 2004. First published April 14, 2004 10.1152/jn.00947.2003. The mechanical properties of individual motor units in the medial gastrocnemius muscle, as well as the whole muscle properties and innervating motor nucleus, were investigated in dietary-restricted, male Fischer 344/DuCrj rats at ages of 4, 7, 12, 21/22, 27, 31, and 36 mo. The tetanic tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
(50 reference statements)
3
13
0
Order By: Relevance
“…These findings have been corroborated by many other studies that have also reported an aging-related reduction in motor unit (MU) number and/or a reduction in both the number and diameters of motor axons in human ventral roots [25-28]. Importantly, this aging-related decline in motor neuron number in humans is also a well-established feature of neuromuscular aging in rodents [22,23,29,30]. …”
Section: Reviewsupporting
confidence: 70%
“…These findings have been corroborated by many other studies that have also reported an aging-related reduction in motor unit (MU) number and/or a reduction in both the number and diameters of motor axons in human ventral roots [25-28]. Importantly, this aging-related decline in motor neuron number in humans is also a well-established feature of neuromuscular aging in rodents [22,23,29,30]. …”
Section: Reviewsupporting
confidence: 70%
“…Previous studies on the contractile properties of ageing rodent whole muscle have examined only males [10][14], [16], [18] or females [15], [19]. To our knowledge, our present study is the first to examine muscles of both male and female mice under identical experimental conditions.…”
Section: Introductionmentioning
confidence: 90%
“…In mice, significant decreases in muscle mass have been reported at ages of 26–27 months [10] to 34–37 months [12]. Assuming an average lifespan of around 36 months in rats [16] and 30 months in mice [17], these results suggest that atrophy only becomes significant in the final 20% or so of the rodent lifespan.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Aging rats have many characteristics in common with humans regarding progressive changes in skeletal muscle architecture and selective loss of Type II alpha motor neurons and fast fibers with age [25,26]. As described above, therapeutic agents which affect muscle size in humans also increase muscle size and function in aging rats and mice [19,27-29].…”
Section: Introductionmentioning
confidence: 99%